MOTIVASI BELAJAR SEJARAH DENGAN STRATEGI PEMBELAJARAN DIRECTED READING THINKING ACTIVITY PADA SISWA KELAS X SMA NEGERI 1 INDRAPURI - Putri Icha Lestari; Husaini; Abdul Azis (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
Learning motivation is one of the important factors influencing students' engagement in the learning process. Low motivation in learning history may result in limited student participation during classroom activities, preventing learning objectives from being achieved optimally. One instructional strategy that can be applied to encourage students' active participation is the Directed Reading Thinking Activity (DRTA). This study aimed to determine (1) the implementation of the Directed Reading Thinking Activity strategy in history learning for tenth-grade students at SMA Negeri 1 Indrapuri and (2) students' motivation in learning history after the implementation of the Directed Reading Thinking Activity strategy. This study employed a quantitative approach using a pre-experimental method with a one-shot case study design. The sample consisted of 20 students selected through purposive sampling. Data were collected through observation and questionnaires and analyzed using descriptive statistics and the Shapiro-Wilk normality test. The results showed that the implementation of the Directed Reading Thinking Activity strategy in history learning was carried out very well, as indicated by the student activity observation results, which reached an implementation percentage of 92%. The questionnaire results revealed that 19 students were categorized as having high learning motivation, while one student was categorized as having low learning motivation. The average motivation score was 68.95, with a success percentage of 95%, which falls into the "Very Good" category. The Shapiro-Wilk normality test yielded a significance value of 0.137 (>0.05), indicating that the data were normally distributed. Therefore, students' motivation in learning history after the implementation of the Directed Reading Thinking Activity strategy was classified as very good. This strategy can be used as an alternative instructional strategy in history learning.